Technology literacy applications in learning environments - Carbonara, David D., 1952- (Hershey, Pa. : Information Science Pub., 2005)
'This book discusses the efficacy of instructional technology in various, global learning environments'--Provided by publisher
Includes bibliographical references and index
Keywords: Educational technology -- Cross-cultural studies; Education -- Effect of technological innovations on -- Cross-cultural studies